2018
DOI: 10.1016/j.micpath.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Resiquimod enhances mucosal and systemic immunity against avian infectious bronchitis virus vaccine in the chicken

Abstract: Adjuvant enhancing mucosal immune response is preferred in controlling many pathogens at the portal of entry. Earlier, we reported that a toll-like-receptor 7 (TLR7) agonist, resiquimod (R-848), stimulated the systemic immunity when adjuvanted with the inactivated Newcastle disease virus vaccine in the chicken. Here, we report the effect of R-848 when adjuvanted with live or inactivated avian infectious bronchitis virus (IBV) vaccines with special emphasis on mucosal immunity. Specific pathogen free (SPF) chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Earlier, we reported the enhancement of antigen-specific humoral and cellular immune responses as well as protection against infection with the virulent Newcastle disease (ND) virus, when R-848, a TLR7 agonist was used with an inactivated ND vaccine in specific pathogen free (SPF) chickens 14 . Recently, we reported the enhancement of antigen-specific systemic and mucosal immune responses when R-848 was used with avian infectious bronchitis virus vaccines 15 , as well as the prophylactic potential of R-848 against infection with very virulent IBDV in SPF chickens 16 . Although a single TLR agonist is capable of inducing potent immune responses, a combination of TLR agonists might minimize the dose and side effects, mimic the natural infection and induce more balanced or desirable immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we reported the enhancement of antigen-specific humoral and cellular immune responses as well as protection against infection with the virulent Newcastle disease (ND) virus, when R-848, a TLR7 agonist was used with an inactivated ND vaccine in specific pathogen free (SPF) chickens 14 . Recently, we reported the enhancement of antigen-specific systemic and mucosal immune responses when R-848 was used with avian infectious bronchitis virus vaccines 15 , as well as the prophylactic potential of R-848 against infection with very virulent IBDV in SPF chickens 16 . Although a single TLR agonist is capable of inducing potent immune responses, a combination of TLR agonists might minimize the dose and side effects, mimic the natural infection and induce more balanced or desirable immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…resiquimod, imiquimod, gardiquimod and ioxoribine) [ 7 , 10 ]. In chickens, ssRNA can induce antibacterial effects against Salmonella Enteritidis [ 11 ] and antiviral effects against infectious bursal disease virus infection [ 12 , 13 ]. Recently, a study demonstrated that ssRNA upregulates mRNA expression of pro-inflammatory mediators including IL-1β and iNOS in chicken in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no further increase in IgA level upon challenge, suggesting the significant role of neutralizing antibodies in reducing the potency of IBV infection at the time of challenge (Joiner et al 2007). In our lab, administration of resiquimod (R-848), a TLR-7 agonist with inactivated or live IBV vaccine increased the secretory IgA, which was mediated through the enhanced expression TGF-β4 in the chicken (Matoo et al 2018).…”
Section: Immunobiologymentioning
confidence: 70%